The Effect Characteristics Board of Directors on The Financial Performance of Sharia Commercial Banks in Indonesia - Ramdani Ramdani; Muhamad Umar Mai; Muhamad Muflih (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Islamic commercial banks in Indonesia have not yet been included in the list of the top Islamic banks in the world with the potential for the largest Muslim population in the world which should be able to make their Islamic commercial banks enter the world's top Islamic banks. The average ROA of Islamic commercial banks is mostly below the ROA standard set by Bank Indonesia (1.5%). This research was conducted at Islamic commercial banks registered with OJK in 2011-2021 and uses secondary data sourced from annual reports. Analysis of this research data using E-Views software viaRandom Effects Model. The results of the analysis prove that board size, BOPO and NPF have a negative effect on ROA. The age of the chairman of the board and the education of the chairman of the board have a positive effect on ROA. The proportion of female boards, FDR, GDP, inflation and remuneration have no effect on ROA, so that the macroeconomic indicators: GDP and inflation have no effect on ROA of Islamic Commercial Banks.